A study of surgical outcomes of myringoplasty in active and inactive ears - Patel, Vasim Ismail; Kulkarni, N. H.; A. C., Jyothi; B. H., ShriKrishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic otitis media (COM) can present with inactive (dry) and active (wet) ear. It’s an accepted fact that an actively draining central perforation is not a contraindication for ear surgery. The discharging ear presents the otologists with the dilemma of operating on it or not, this is due to widespread belief that the success rate while doing ear surgeries on active ears is decidedly inferior. Hence the present study is intended to find the outcome of ear surgeries in inactive and active ear with objective to find the incidence of graft uptake and hearing improvement in both the groups. Methods: A total of 50 active ear (with mucoid discharge) and 52 inactive ears (not discharging at least 3 month before surgery) with mucosal chronic otitis media underwent myringoplasty with cortical mastoidectomy. Graft take and hearing gain rates 3 and 6 months after surgery were calculated for both groups and compared. Results: The graft take rate was 90% for the active ear group and 94% for the inactive ear group. The hearing gain rate was 90% for the active ear group and 94% for the inactive ear group. Differences were found to be statistically insignificant for both graft intake (p=0.461) and hearing gain (p=0.543). Conclusions: The success of myringoplasty is not adversely affected by the presence of mucoid ear discharge at time of surgery, and outcomes are comparable to those of the opration done for inactive ears.